The shaky supply side. On neoclassical “anomalies” in macroeconomic theory - SKARSTEIN, R. (PSL Quarterly Review, 2013)
It is notable that neither the “New Classicals” nor the “New Keynesians” take much notice of Keynes’ important article of 1939, where he self-criticised precisely the supply-side assumptions in his General Theory. The present work deals with some of these problems, making references particularly to Keynes’ 1939 article and to empirical studies with a bearing on the supply-side postulates in macroeconomics. JEL: E12